Urgensi Penanaman Nilai Agama dan Moral Sejak Dini untuk Mencegah Kasus Bullying - Yuniar, Dias Putri; Safitri, Maria; Adiba, Sarah; Riskiyah, Fadilatur; Agustin, Alief; Faricha, Dewi; Karimah, Nabilatul (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
The most prevalent form of violence currently encountered in Indonesia is bullying, which occurs frequently among children from elementary to high school. Bullying has negative impacts on the victims, perpetrators, and those who witness it. It is a primary factor in the deterioration of mental health. Therefore, it is crucial to educate children about bullying from an early age to prevent such incidents. This study aims to provide solutions to prevent bullying. The method used in this research is a literature review. The findings indicate that bullying occurs due to several factors, including children imitating scenes from gadgets, television, and even violent behavior from their parents, among others. The proposed solution to prevent bullying involves instilling moral and religious values in children from an early age, ensuring they are educated about the dangers of bullying and do not engage in such behavior. Teachers and parents play a critical role in instilling these values in young children. This research contributes to the existing literature by highlighting the importance of early education in moral and religious values as a preventive measure against bullying. It underscores the pivotal roles of parents and teachers in shaping children's understanding and behavior regarding bullying. By addressing the root causes and promoting early intervention, this study provides a framework for reducing the incidence of bullying and its associated negative outcomes in the school environment